Correction to: Qualitative Assessment of Adult Patients' Perception of Atopic Dermatitis Using Natural Language Processing Analysis in a Cross-Sectional Study - Bruno Falissard; Eric L. Simpson; Emma Guttman-Yassky; Kim A. Papp; Sebastien Barbarot; Abhijit Gadkari; Grece Saba; Laurene Gautier; Adeline Abbe; Laurent Eckert (Adis, Springer Healthcare, 2020)
The authors would like to correct the images in figures which are in wrong order and require swapping.